THE EXISTENCE OF THE TAREKATE IN THE HISTORY OF ISLAM IN JAVA AND ITS APPLICATIONS IN INDONESIAN HIGHER EDUCATION - Duriyah; Ahmad Asmuni (Al Naqdu, 2025)
This research aims to actualize the existence of the tarekat on the island of Java from a historical perspective and analyze its application in universities. The research uses a qualitative approach with locations in Central Java. Participants consisted of two mursyid of the tarekat and ten practitioners of the tarekat. Data was collected through observation, interviews, and documentation. The focus of the research includes two main themes: the existence of the tarekat on the island of Java in the period 2000–2020 and the application of the values of the tarekat in universities in Indonesia. The results of the study show that the tarekat in Java continues to exist despite the technological and cultural advances of millennials. The sustainability of the tarekat is supported by the spirit of nationalism instilled by the mursyids, a simple organizational management system, and a strong tradition of yellow book literacy. Meanwhile, the application of tarekat values in higher education is reflected in three main aspects, namely strengthening nationalism, implementing effective organizational management, and developing a literacy culture. Thus, the tarekat not only survives as a spiritual practice, but also contributes to the formation of national character and values in the context of higher education in Indonesia